Combining virtual reality enabled simulation with 3D scanning technologies towards smart manufacturing - Hutabarat, Windo; Oyekan, John; Turner, Christopher J.; Tiwari, Ashutosh; Prajapat, Neha; Gan, Xiao-Peng; Waller, Anthony (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Recent introduction of low-cost 3D sensing and affordable immersive virtual reality have lowered the barriers for creating and maintaining 3D virtual worlds. In this paper, we propose a way to combine these technologies with discrete-event simulation to improve the use of simulation in decision making in manufacturing. This work will describe how feedback is possible from real world systems directly into a simulation model to guide smart behaviors. Technologies included in the research include feedback from RGBD images of shop floor motion and human interaction within full immersive virtual reality that includes the latest headset technologies.